Peningkatan Hasil Belajar Siswa Melalui Metode Diskusi Pada Mata Pelajaran PAI di Kelas IV SD Negeri 17 Sungai Pandahan - Umar, Syarifah (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to analyze the implementation of the discussion method in Islamic Religious Education (PAI) to improve students' learning outcomes at SDN 17 Sungai Pandahan. The research method used is Classroom Action Research (CAR) with four stages: planning, acting, observing, and reflecting. The results of the study show that the application of the discussion method successfully improved students' learning outcomes, as reflected in the increase in the percentage of learning completeness from 50% in the pre-cycle to 68.75% in the first cycle, and 81.25% in the second cycle. The discussion method also increased student engagement and enthusiasm in learning, although some students still faced difficulties in relating the material to daily life experiences. Therefore, additional approaches are needed to assist students who struggle in understanding the material.